Evaluation of anti‐EGFR potential of quinazoline derivatives using molecular docking: An in silico approach. (3rd June 2021) - Tanveer, Fariha; Anwar, Muhammad Faraz; Siraj, Bushra; Zarina, Shamshad
Abstract: Overexpression of epidermal growth factor receptor (EGFR) is commonly reported in epithelial malignancies such as oral squamous cell carcinoma. Inhibition of EGFR is, therefore, considered a potential therapeutic strategy. Among various anti‐EGFR drugs, quinazoline‐based tyrosine kinase inhibitors (TKIs) have gained increasing attention. Present study focused to investigate anti‐EGFR potential of quinazoline‐based compounds using in silico approach. Two widely used docking programs GOLD and AutoDock Vina were used for the study. Four drugs were docked on the X‐ray crystallographic EGFR structure (1XKK). GOLD and AutoDock Vina produced results in terms of fitness score and binding affinity, respectively. GOLD prioritized varlitinib and AutoDock Vina preferred imatinib over other drugs. To reach the consensus from both software, all four drugs coupled with EGFR were studied rigorously. GOLD demonstrated varlitinib to be the best inhibitor with highest fitness score of 109, whereas AutoDock Vina revealed imatinib as the potent ligand with least binding energy of −10.9 kcal/mol. Most stable hydrogen bonds observed by GOLD and maximum number of hydrophobic contacts along with strong ionic interaction exhibited by varlitinib through both software have led us to conclude varlitinib as the most potent EGFR inhibitor in the studied group. Abstract : Overexpression of epidermal growth factor receptor (EGFR) is commonly reported in epithelial malignancies such as oral squamous cell carcinoma.